The Effect of Low-Carbon Technology on Carbon Emissions Reduction in the Building Sector: A Case Study of Xi’an, China - Dongyi Zhang; Lu Sun; Yifan Zhang; Tianye Liu; Lu Gao; Fufu Wang; Xinting Qiao; Yuqi Liu; Jian Zuo; Yupeng Wang (Buildings)
Efficient carbon reduction pathways in the building sector are critical for urban decarbonization. This study predicts urban carbon emissions and establishes models to evaluate the carbon emission reduction potential of applying building low-carbon technologies (LCTs) at the urban scale. The models under consideration encompass a spectrum of active strategies, specifically heat pump (HP), rooftop photovoltaic (PV) systems, and smart heating, ventilation, and air conditioning (HVAC) systems, alongside passive strategies encompassing advanced building materials and building envelopes. The predictive calculations consider building typologies, technological evolution, adoption rates, and local policy constraints. Results indicate that by 2030, the building sector in Xi’an will account for over 30% of the city’s total carbon emissions. The integrated emission reduction effect of LCTs reaches 25.8%, with building materials contributing the most significantly at 9%. Notably, rooftop PV systems demonstrate the highest carbon reduction potential among active strategies, while HP exhibits the fastest annual growth rate in mitigation. Furthermore, the study evaluates the feasibility of these LCTs to accelerate progress toward carbon reduction goals in the building sector.